Dyskinesia as a new adverse effect of hormonal treatment in West syndrome. Issue 1 (March 2014) - Sukhudyan, Biayna G.; Dimova, Petia S.; Capuano, Alessandro; Vigevano, Federico
<x xml:space="preserve">Abstract</x> West syndrome is an age‐dependent epileptic encephalopathy. Despite potential side effects, hormonal therapy remains the main treatment for West syndrome. Here, we report on 10 patients receiving steroid treatment who presented with unusual, mostly hyperkinetic, movements. Facial grimacing, repetitive mouth opening, adduction and abduction of upper and lower extremities, and periodical strabismus in different combinations were observed in all patients, independent of formulation, dose, duration, and efficacy of treatment. Symptoms disappeared in sleep and reappeared immediately on arousal. Dyskinesias stopped gradually after a month of discontinuation of treatment. Repeated EEGs did not show corresponding epileptiform activity. We conclude that these abnormal movements can be attributed to side effects of hormonal treatment. [Published with video sequences]